Penerapan PSAK No. 46 pada PT. Telkom Indonesia (Persero) Tbk. - Detti Meilandri (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to analyze the implementation of the Pernyataan Standar Akuntansi Keuangan (PSAK) No. 46 on Income Taxes in the financial statements of PT. Telkom Indonesia (Persero) Tbk. for the 2022-2023 period. PSAK No. 46 regulates the treatment of income taxes resulting from temporary differences between accounting and tax bases, which impact the recognition of deferred tax assets and deferred tax liabilities in the company's financial statements. Using a descriptive exploratory non-statistical method, this study evaluates the extent to which PT. Telkom Indonesia applies this standard in managing its tax obligations and disclosing relevant information in its financial statements. The study results indicate that PT. Telkom Indonesia has implemented PSAK No. 46 effectively, with temporary and permanent differences recorded in accordance with standard provisions. The fiscal adjustments made reflect the reconciliation between commercial and fiscal financial statements, which affect the company's current and deferred taxes. Furthermore, the statement of financial position and income statement have separately presented deferred tax accounts, enhancing transparency and compliance with applicable accounting standards. This study confirms that the application of PSAK No. 46 by PT. Telkom Indonesia supports the preparation of more accurate and credible financial statements that comply with prevailing tax regulations in Indonesia. These findings provide insights for other companies in managing income taxes and aligning their financial statements with evolving accounting standards.